The Effect of the Group Investigation (GI) Type Cooperative Learning Model Based on Experimental Skills on Generic Skills in the Kinetic Theory of Gases Material in the Classroom XI Interest IPA Senior High School Negeri 3 Medan Semester II Academic Year 2024/2025 - Pinondang Hutapea; Melda Panjaitan (Cattleya Darmaya Fortuna, 2025)
The objectives of this study are: (1) To determine the differences in generic skills due to the effects of the GI type cooperative learning model and the DI model in class XI of SMA Negeri 3 Medan (2). To determine the differences in generic skills of students who have high laboratory skills and low generic skills in class XI of SMA Negeri 3 Medan (3) To determine whether there is an interaction between the GI type cooperative learning model and the DI learning model with laboratory skills on students' generic skills. The sampling technique used a purposive sample consisting of two classes with a total sample of 72 students. The research instrument was a learning achievement test and a questionnaire on students' generic skills. The test used to obtain data was in the form of multiple choices. The data in the study were analyzed using SPSS 28 with two-way ANOVA. The results of the ANOVA test obtained: 1. The generic skills of learning physics of students taught with the GI type cooperative learning model are higher than the physics learning achievement of students taught with the DI learning model. 2. The physics learning achievement of students who have high generic skills is higher than the physics learning achievement of students who have low generic skills. 3. There is an interaction between the GI type cooperative learning model and laboratory skills on students' generic skills.